Analytical Laboratory at Dearborn Chemical Company facility - Dearborn Chemical Company (1955)
General view of employees (left to right) Ruth Johnson Dugo, Lillian Kazmierzki, Valentine I. Miciulis, and Serge Levicki at work in the Analytical Laboratory at the Dearborn Chemical Company's 35th Street laboratory facility located in Chicago, Illinois. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers and cooling towers.
Keywords: Women in science; Employees; Chemical industry; Laboratories; Water purification chemicals industry; Corporations; Women employees; Glassware; Dearborn Chemical Company; Scientific apparatus and instruments; Dugo, Ruth Johnson; Kazmierzki, Lillian; Miciulis, Valentine I.; Levicki, Serge